Association between hematological inflammatory markers and clinicopathological features in gastric cancer patients received adjuvant radiotherapy - ALKIŞ, HİLAL (My University, 2023)
BACKGROUND:Hematological inflammatory markers may be used as predictors for prognosis of gastric cancer. The aim of this study was to investigate the the association between pre-treatment hematological inflammatory markers and clinicopathological features in the gastric cancer patients. METHODS: We retrospectively enrolled 118 patients diagnosed with gastric cancer who underwent surgery and received adjuvant chemoradiation at the Department of Radiation Oncology between July 2013 and June 2023. Clinicopathologic features such as age (≤50 and >50 years of age), sex, tumor location (cardia, corpus, antrum), T and N stage, histological type (adenocarcinoma, nonadencarcinoma), grade, lymphovascular invasion (LVI), and perineural invasion (PNI) were reviewed. Preoperative hematological inflammatory markers are neutrophil, lymphocyte, monocyte, platelet, mean platelet volume (MPV), plateletcrit, neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and platelet to lymphocyte ratio (PLR) were recorded. RESULTS: Median age was 59 (23-85) years. Median age for men (n=89) and women (n=29) was 58 (29-85) and 61 (23-83) years, respectively. NLR, LMR, and PLR were found to be 2.8 (±1.51), 3.38 (±1.18), and 153.44 (±59.8), respectively. LMR was significantly higher in patients ≤50 years of age compared to those over 50 years (p= 0.02). While LMR was 3.26 (±1.16) in the patients ≤50 years of age, it was 3.86 (±1.15) in older ones. Neutrophil values and NLR were found moderately higher in men compared to women [5.2 (±2.05) vs. 4.3(±1.8) and 2.95 (±1.6) vs. 2.3 (±1.2), respectively] (p=0.04). There was a strong correlation between the T stage and platelet values (p= 0.006). Platelet value was found to be 167.5 (±61.3), 310.4 (±62.2), 270 (±56.1), and 275.2 (±71.2) in patients with T1, T2, T3, and T4, respectively. Other hematological inflammatory markers were not found to affect the clinicopathological features of the gastric cancer patients. CONCLUSIONS: LMR, NLR and platelets are the hematological inflammatory markers which present relationship with clinicopathological features of the gastric cancer patients.
Keywords: Inflammatory markers; gastric cancer; clinicopathological features